Assessing students’ focus and interest using youtube analytics - Zamira Hasanah Zamzuri, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Knowing the fact whether your students are paying attention in the class is a valuable information that helps educators to reassess their teaching quality. With the recent global situation, opting to the recorded or online streaming session has become more common and needed. Various platforms are available in order to share these sessions and one of the most commonly used is YouTube. One attractive property offered by YouTube is the analytics are readily available for each video with various important and interesting facts. From these facts, the educators are able to assess the students’ focus and further strategizing for the future lessons. Based on the data of 22 videos uploaded on October 2020 to January 2021, the average view of duration for each video is around 10 to 12 minutes, which is approximately one third from the total duration of the video. The students were giving more attention to the demonstration sessions, when white board being used and visualizations are shown in the videos. Less interest is observed from the students when the video contents are chapters’ summary or the formulas.